Gender-affirming hormone therapy and cardiovascular risk: an umbrella review of meta-analyses - Moon, Hyunoh; Park, Sejin; Lee, Yeongin; Lee, Seo Hyun; Lim, Chaeseong; Cho, Su-Yeon; Kwon, Yujin; Cho, Won Ho; Kim, Hyun-Joo; Kim, Won Kyu; Kim, Kihun; Kim, Yun Hak (TAYLOR & FRANCIS INC, 2025)
Introduction Gender-affirming hormone therapy (GAHT) is widely used to help transgender individuals align physical traits with gender identity, yet concerns remain regarding its cardiovascular safety. Previous reviews have produced conflicting findings, often constrained by small sample sizes, short follow-up, and heterogeneous hormone regimens. This umbrella review synthesizes current meta-analytic evidence on cardiovascular outcomes of GAHT. Methods We followed PRISMA guidelines and searched Embase, MEDLINE, Scopus, Web of Science, and ScienceDirect through February 2025. Eligible studies were meta-analyses reporting quantitative outcomes of GAHT. Data were extracted on lipid profiles, blood pressure, hematocrit, and cardiovascular events. Pooled estimates were calculated using inverse-variance methods. Study quality was assessed with AMSTAR 2, and evidence certainty was graded with GRADE. Results Eight meta-analyses including 30,789 participants were reviewed. Among individuals assigned female at birth (AFAB), GAHT increased low-density lipoprotein, triglycerides, and total cholesterol and decreased high-density lipoprotein. Blood pressure showed no significant change. Among individuals assigned male at birth (AMAB) receiving estradiol, lipid effects were inconsistent. Hematocrit increased predominantly in the AFAB group. VTE prevalence was 0.01 in AFAB and 0.02 in AMAB, while risks of myocardial infarction and stroke were not significantly different. The overall quality of evidence ranged from moderate to low. Conclusions GAHT affects lipid metabolism, especially among AFAB individuals, but current data do not indicate a significant increase in cardiovascular events. Given the short follow-up and heterogeneity of study designs, further high-quality research is warranted to guide clinical care.